2018
DOI: 10.1016/j.eurpolymj.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Ionic polymer actuators using poly(ionic liquid) electrolytes

Abstract: In this work, poly(ionic liquid) (polyIL) polymer electrolytes were prepared by the free radical copolymerization of IL monomers with a plasticizing monomer having poly(ethylene glycol) (PEG) side chain. The IL monomers, i.e., the polycation and polyanion precursors, were 1-[(3-methacryloyloxy)propyl]-3-methylimidazolium bis(trifluoromethanesulfonyl)amide ([C 3 mim-MA][TFSA]) and 1-methyl-3-propylimidazolium N-[3-(methacryloyloxy)propylsulfonyl]-N-(trifluoromethanesulfonyl)amide ([C 3 mim][TFSA-MA]), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 31 publications
0
51
2
Order By: Relevance
“…In addition, the tunable polarity of ILs prevents the adverse dissolution of active materials, such as water [ 37 ], and various structures of ILs are proposed by simple synthesis [ 38 ]. Because of these properties, ILs for various electrochemical devices, such as SCs, FCs, LIBs, solar cells, and actuators, have been researched [ 37 , 41 , 42 , 43 , 44 , 45 , 46 ]. ILs consist of a large organic cation, such as imidazolium, ammonium, and pyrrolidinium, with a variety of anions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tunable polarity of ILs prevents the adverse dissolution of active materials, such as water [ 37 ], and various structures of ILs are proposed by simple synthesis [ 38 ]. Because of these properties, ILs for various electrochemical devices, such as SCs, FCs, LIBs, solar cells, and actuators, have been researched [ 37 , 41 , 42 , 43 , 44 , 45 , 46 ]. ILs consist of a large organic cation, such as imidazolium, ammonium, and pyrrolidinium, with a variety of anions.…”
Section: Introductionmentioning
confidence: 99%
“…PILs/IL-based polymers conjugate the properties of the ionic liquids (e.g., ionic conductivity, negligible vapor pressure, and thermal stability) with those from polymers (e.g., functionalization, viscoelastic properties, and 3D structure) [ 50 ]. Recently, IL-based copolymers ionic EAPs were developed for soft actuators and promising tissue engineering scaffolds applications [ 12 , 51 ].…”
Section: Conventional Technologies and Most Common Polymers To Produce Eapsmentioning
confidence: 99%
“…Kokubo et al developed IL-based copolymers ionic polymer actuators and studied the influence of polyelectrolyte structure (polycationic or polyanionic) in the bending performance [ 51 ]. Crosslinked polymer electrolytes were prepared by free-radical copolymerization of cationic IL monomer (1-[(3-methacryloyloxy)propyl]-3-methyl imidazolium bis(trifluoromethanesulfonyl)amide, [PMIm-MA][TFSA]) or anionic IL monomer (1-methyl-3-propylimidazolium N-[3-(methacryloyloxy)propylsulfonyl]-N-(trifluoromethanesulfonyl)amide, [PMIm][TFSA-MA]) with poly(ethylene glycol) methyl ether methacrylate (PEGMEN) plasticizer, crosslinked by ethylene glycol dimethacrylate (EGDMA, 2 mol% of the total monomers).…”
Section: Conventional Technologies and Most Common Polymers To Produce Eapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer networks containing ionic species have received attention as functional materials in liquid/gas separations, [9][10][11][12][13][14][15] soft actuators, [16][17][18][19][20] ion exchange membranes, [21][22][23][24][25] and electrolytes for energy storage. [26][27][28][29][30][31][32][33][34][35] In the context of lithium conduction, polyethylene oxide (PEO) networks with added lithium salts have been investigated and it was shown that covalent crosslinking can significantly reduce the crystallinity and increase the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%